IMPLEMENTASI CORPORATE SOCIAL REONSIBILITY OLEH BADAN USAHA MILIK DAERAH TERHADAP PELESTARIAN LINGKUNGAN DAERAH ALIRAN SUNGAI BENGAWAN SOLO DI KOTA SURAKARTA - Sudarwanto S, AL. Sentot; Ciptorukmi N., Anjar Sri (Yustisia, 2012)
AbstractThis research using juridical empiric approach and incorporated as evaluative-descriptive research by using analysis-qualitative methods. We are using primary and secondary source for our research source. We are using proficient and competent informant that work at PDAM and TSTJ. In order to choose our informant, we are using purposive sampling method. We also use interview and literature study in order to gather data for this research. As the conclusion we can assume that implementation of Corporate Social Responsibility of PDAM Surakarta basically already meet the Surakarta’s Local Government Regulation No. 1 Year 2004 regarding Amendment of Surakarta local government regulation No. 3 year 1977, Regulation No.5 year 1962, Regulation No, 32 year 2009. On the other hand, TSTJ Surakarta practically haven’t done Corporate Social Responsibility. Nevertheless, they have done the internal conservation by doing reforestation program in TSTJ Surakarta area. Revitalization of Local Government-Owned Corporation in Surakarta has been done in order to create Good Corporate Governances Awareness for the manager of the Local Government-Owned Corporation. Regulation No.5 year 1962 need to be revised by accommodating Corporate Social Responsibility and synchronized with regulation No.32 year 1934 regarding local governance.Keywords:Corporate Social responsibility, Local Government-Owned Corporation, Bengawan Solo’s WatershedAbstrakPenelitian ini menggunakan pendekatan yuridis empiris dan disusun sebagai suatu penelitian deskriptif-evaluatif dengan menggunakan metode analisis kualitatif. Sumber data yang digunakan baik sumber data primer maupun sekunder. Informan yang digunakan adalah informan yang layak dan kompeten dari PDAM dan TSTJ. Informan dipilih menggunakan teknik purposive sampling. Pengumpulan data menggunakan wawancara dan studi pustaka. Hasil penelitian menunjukkan bahwa implementasi Tanggungjawab Sosial Perusahaan (CSR) dari PDAM secara prinsip telah sesuai dengan Keputusan Pemerintah Kota Surakarta No. 1 Tahun 2004 tentang Perubahan atas Peraturan Daerah Kotamadya Tingkat II Surakarta No. 3 Tahun 1977, UU No. 5 tahun 1962 dan UU No.32 Tahun 2009. Di sisi lain, TSTJ secara spesifik belum melaksanakan (CSR). Namun, TSTJ telah melakukan konservasi internal antara lain dalam bentuk penanaman pohon di wilayah Perusahaan Daerah TSTJ. Revitalisasi BUMD Kota Surakarta harus dilakukan untuk mewujudkan pengelola yang menerapkan prinsip Good Corporate Governance. Undang-Undang Nomor 5 Tahun 1962 tentang Perusahaan Daerah perlu direvisi untuk mengakomodir peraturan tentang CSR yang disinkronkan dengan Undang-Undang Nomor 32 Tahun 2004 tentang Pemerintah DaerahKata Kunci: Tanggung Jawab Sosial Perusahaan, Badan Usaha Milik Daerah, revitalisasi